A marine fibrinolytic compound FGFC1 stimulating enzymatic kinetic parameters of a reciprocal activation system based on a single chain urokinase-type plasminogen activator and plasminogen. (May 2018) - Guo, Ruihua; Duan, Dong; Hong, Shaotong; Zhou, Yu; Wang, Fang; Wang, Shujun; Wu, Wenhui; Bao, Bin
Graphical abstract: FGFC1, a kind of bisindole alkaloid from a metabolite of the rare marine fungi Starchbotrys longispora FG216, modulated enzymatic kinetic parameters including the fibrinolytic reaction rate and fibrin degradation characteristics. Highlights: A enhancing fibrinolysis mechanism for Fungi fibrinolytic compound 1 (FGFC1) from Starchybotrys longisporais proposed. The fibrinolysis was based on the enzymatic reaction of a chromogenic-substrate associated with p -nitroaniline. k cat and k cat/ Km increased with an increase of FGFC1 concentration. Abstract: A marine fibrinolytic compound FGFC1 enhancing fibrinolysis was obtained involving enzymatic kinetic parameters of a reciprocal activation system with a single chain urokinase type plasminogen activator and plasminogen. FGFC1, a kind of bisindole alkaloid from a metabolite of the rare marine fungi Starchbotrys longispora FG216, modulated enzymatic kinetic parameters including the fibrinolytic reaction rate and fibrin degradation characteristics. The enzymatic kinetics of fibrinolysis was described based on the enzymatic reaction of a chromogenic-substrate associated with p -nitroaniline ( p -NA). While the single chain urokinase-type plasminogen activator (pro-uPA) activated plasminogen, k cat and k cat / K m increased significantly with an increase of FGFC1 concentration. Moreover, k cat and k cat / K m exhibited 26.5-fold and 22.8-fold enhanced activity at the concentration of 40 μg mL −1 of FGFC1, respectively. The results suggested that FGFC1 significantly improved the maximum catalytic efficiency and the total catalytic activity of fibrinolysis base on the reciprocal activation of pro-uPA and plasminogen. K m increased with increasing FGFC1 concentration, which indicated that FGFC1 slightly decreased the affinity activity of the pro-uPA and plasminogen versus the enzyme substrate. The marine bisindole alkaloid FGFC1 enhanced fibrinolysis, which was taken on enzymatic kinetic characteristics.